Diuretic Resistance in Advanced Heart Failure - Anita Surya Santoso; Mohammad Saifur Rohman; Indra Prasetya; Budi Satrijo (Heart Science Journal, 2021)
Advanced heart failure (HF) is used to characterized patients in HF with severe symptoms, recurrent decompensation and severe cardiac dysfunction. The prevalencekof HFkis approximatelyg1-2% of thecadult population inhdeveloped countries and it will be rising more than 10%pamongapeoplec>70ayears of age, whereas estimated theoprevalence ofcpatients with advanced HF is about 1% until 10%cof thekoverallkHFopopulation. Most ofkthe HF hospitalizationssare due to signs and symptoms of fluidcoverload.Recurrent congestionccould worsen patientssoutcomes.Loopdiureticssare recommended for thectreatmentcofkcongestionqinprHF patient. cHowever,cdiureticvresistanceeispavcommon problem issueiinpacuteqdecompensationtofcadvancedochronicrheartwfailureq(ACHF) patients and established prognostic factor. Some early reports estimated the prevalence of diuretic resistance about 20%-30% in HF population. In this review, we will be discuss how to diagnose the advancedvheartufailurepand the underlying mechanism of diuretic resistancebin HF patients. We also describe pharmacologicalvand non-pharmacologicalstrategies to overcome this issue.